Fuzzy-proportional-integral-derivative hybrid controller design for ultra-high temperature milk processing - Ahmad, Naseer; Arsalan, Muhammad (IAES International Journal of Robotics and Automation (IJRA), 2023)
In the ultra-high temperature (UHT) process, fluid temperature is raised above 135 °C for a short period of time (typically 4 seconds) and then quickly cooled ensuring no microbes remain in the final product. To have better quality processed milk, a stringent temperature control system is necessary. To solve this problem a detailed control-oriented mathematical model of the heating system for UHT application is developed and a detailed block diagram is established by identifying various systems and signals. To draw the merits of a feedforward controller (transfer function or fuzzy logic based) and proportional-integral-derivative (PID) feedback compensator, a fuzzy PID hybrid controller is designed and simulated in a MATLAB environment. Findings of the simulation results indicate that the fuzzy-PID hybrid compensator concatenates the benefits of both controllers. PID controller processes the error signal and tracks the setpoint whereas the feedforward controller (transfer function or fuzzy) effectively rejects the disturbance signal’s effect on the controlled variable. The fuzzy-PID hybrid controller performs better than the individual PID or fuzzy controller.